THE EFFECT OF OLD AND THE VOLUME OF WATER BOILING IS DIFFERENT ON THE SALT CONCENTRATION AND CHEMICAL COMPOSITION OF FISH MEAL IS MADE FROM SALTED BY - CATCH - Gusti Putra Yunius; Bustari Hasan; Rahman Karnila (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2015)
Fish meal prepared from salted by-catch contained a very high saltconsentration, therefore it must be reduced to prevent its effect to feedconsumption and growth of fed animals. This research was intended to evaluatethe effect of boiling time and water volume on salt reduction of fish meal preparedfrom salted by-catch. Salted by-catch comprised of various fish species, wasobtained from the trash fish supplier in Kampar. The fish was cleaned and boiledin boiling water with ratio of fish and bloiled water was 1: 2, 1: 3, 1: 4respectively for 15, 30 and 45 minutes. The fish was dried and grinded to fish2JOM: OKTOBER 2015meal. The effect of boiling was evaluated of salt concentration, proksimatecomposition, and NPN concentration. The results showed that the saltconcentration of by-catch reduced as the longer boiling time and the higherboiling water volume. Protein composition, moisture and fat also reduced, but ashand NPN were slightly increased as the longer the boiling time and the higherboiling boiling water volume. Boiling time of 30 minutes and ratio of fish toboiling water volume of 1:2 might be the choice as they could reduce saltconcentration and maintained protein concentration relatively. Salt, protein, fat,NPN, moisture, and ash concentration of the fish meal was 2,02%, 20,81%,2,73%, 0,27%, 10,85%, and 49,25% respectively.Key word: Long boiling, boiling water volume, salt trash fish, fish meal,salinity, proximate composition, levels of NPN